PENGARUH KEAHLIAN AUDIT, SELF EFFICACY, DAN KOMPLEKSITAS TUGAS TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN DIMEDIASI OLEH AUDIT JUDGMENT (Studi Empiris pada BPK RI Perwakilan Provinsi Sulawesi Selatan) - Muh Amrih; Murdifin Haming; Asriani Junaid (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
This study aims to examine the effect of audit expertise, Self Efficacy, and the complexity of the task on the auditor's ability to detect fraud mediated by audit judgment at the Republic of Indonesia's Republic of Indonesia BPK Representatives. This research was conducted at the Republic of Indonesia BPK Representative of South Sulawesi Province. This study uses primary data by conducting direct research by providing questionnaires to 56 respondents who are BPK auditors. Data analysis method used is analysis of Structural Equation Model (SEM). The results showed that: audit expertise variables and Self Efficacy variables had a positive and significant effect on audit judgment, while task complexity variables had a negative and significant effect on audit judgment. Audit skill variables and Self Efficacy variables have a positive but not significant relationship to the auditor's ability to detect fraud, while task complexity has a positive and significant influence on the auditor's ability to detect fraud. Audit expertise variables and Self Efficacy variables have a positive and significant influence on the auditor's ability to detect fraud through audit judgment, while task complexity variables have a negative and significant effect on the auditor's ability to detect fraud through audit judgment. Audit judgment variables have a positive and significant effect on the auditor's ability to detect fraud.